2013
DOI: 10.2169/internalmedicine.52.0474
|View full text |Cite
|
Sign up to set email alerts
|

Is Neuroinflammation Involved in the Development of Dementia in Patients with Parkinson's Disease?

Abstract: Objective High-sensitivity C-reactive protein (hs-CRP) is an extremely sensitive systemic marker of inflammation and tissue damage, and increased levels of hs-CRP are strongly associated with inflammatory reactions. Microglia-mediated neuroinflammation has been hypothesized to play an important role in the pathogenesis of idiopathic Parkinson's disease (PD). However, the clinical value of the hs-CRP level in patients with PD is poorly defined. Therefore, we conducted this study to analyze the differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…Epidemiological studies and PD models indicate that aging is the strongest risk factor for PD. Therefore, it has been hypothesized that microglia-mediated neuroinflammation plays an important role in the pathogenesis of PD [4,5]. However, the present study did not show a significant correlation between the serum hs-CRP level, a sensitive marker of systemic inflammation, and aging of patients with PD.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Epidemiological studies and PD models indicate that aging is the strongest risk factor for PD. Therefore, it has been hypothesized that microglia-mediated neuroinflammation plays an important role in the pathogenesis of PD [4,5]. However, the present study did not show a significant correlation between the serum hs-CRP level, a sensitive marker of systemic inflammation, and aging of patients with PD.…”
Section: Discussioncontrasting
confidence: 90%
“…At the cellular level, significant microglial inflammation is observed in regions of dopaminergic degeneration, and some protection against PD is offered by long-term anti-inflammatory medications [4,5,25]. In addition, microglia-mediated neuroinflammation has been hypothesized to play an important role in the pathogenesis of neurodegenerative diseases such as PD and AD [5,6,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased peripheral cytokine production influences PD progression [14,15]. In-Uk Song et al [16] reported that the hs-CRP and fibrinogen levels were significantly higher in the PD patients than in the healthy control group. Our results are similar to those of In-Uk Song et al The epidemiological studies of Chen et al reported that chronic use of NSAIDs reduces the risk of development of sporadic PD.…”
Section: Discussionmentioning
confidence: 99%